Urban sanitation technology decision-making in developing countries: a critical analysis of process guides. Issue 2 (2nd July 2016) - Ramôa, A.; Lüthi, C.; McConville, J.; Matos, J.
Abstract : Planning for urban sanitation in developing contexts is one of the major development challenges of this century. Particularly, the relevance of a broad perspective in sanitation decision-making processes has been increasingly discussed. One possible contribution to achieve comprehensive decisions is through the use of planning guidelines, also called process guides. The present work first identified categories of relevant decision elements, namely: (a) the multi-sectoral approach, (b) the multiplicity of sustainable dimensions, (c) the system analysis perspective and (d) the co-existence of planning scales. Then, for each category, a comparative analysis of urban sanitation process guides was conducted with a focus on technology decision-making. It was found that the importance of considering those categories is increasingly reflected in process guides, although not always in a detailed supportive way. Recommendations are provided to increase the added value of process guides regarding technology selection, as well as, to better integrate them into urban planning.